Pengembangan Bahan Ajar Digital Berbasis Leksikon Arsitektur dalam Mempertahankan Eksistensi Rumah Lontiok - Azlin Resiana; Ermi Rosmita; Basyarul Aziz (eScience Humanity Journal, 2026)
The rapid advancement of technology has also influenced the field of education, requiring educators in the era of the Industrial Revolution 4.0 to innovate by integrating technology into the learning process. The limited availability of learning materials, especially in the Linguistic Anthropology course—which mainly consists of textbooks and PowerPoint slides—has led to low student engagement and affected learning outcomes. This study aims to develop interactive digital learning materials to create effective and efficient learning while preserving local wisdom. Using the Research & Development (R&D) method with the R2D2 (Reflective, Recursive, Design, and Development) model, data were collected through observation, interviews, questionnaires, and tests involving students of the Cultural Anthropology Department at the Indonesian Institute of the Arts Padang Panjang. The validity test results showed that interactive digital learning materials based on Lontiok house architecture received a positive response from validators (93.13%, highly feasible), while practicality tests with students and lecturers showed a 95% practicality level. The average improvement in students’ learning outcomes reached 20.0 or 0.72 (high category), indicating that the developed materials are highly effective for learning about the relationship between language and culture in the Linguistic Anthropology course.